Phylogenomics and metabolic engineering reveal a conserved gene cluster in Solanaceae plants for withanolide biosynthesis - Samuel Edward Hakim; Nancy Choudhary; Karan Malhotra; Jian Peng; Arne Bültemeier; Ahmed Arafa; Ronja Friedhoff; Maximilian Bauer; Jessica Eikenberg; Claus-Peter Witte; Marco Herde; Philipp Heretsch; et al. (Nature Communications)
Abstract Withanolides are steroidal lactones from nightshade (Solanaceae) plants with untapped drug potential due to limited availability of minor representatives caused by lack of biosynthetic pathway knowledge. Here, we combine phylogenomics with metabolic engineering to overcome this limitation. By sequencing the genome of the medicinal plant ashwagandha (Withania somnifera) and comparing it with nine Solanaceae species, we discover a conserved withanolide biosynthesis gene cluster, consisting of two sub gene clusters with differing expression patterns. We establish metabolic engineering platforms in yeast (Saccharomyces cerevisiae) and the model plant Nicotiana benthamiana to reconstitute the first five oxidations of withanolide biosynthesis, catalysed by the cytochrome P450 monooxygenases CYP87G1, CYP88C7, and CYP749B2 and a short-chain dehydrogenase/reductase, producing the aglycone of withanoside V. Enzyme functions are conserved within both sub gene clusters in W. somnifera and between W. somnifera and Physalis pruinosa. Our work sets the basis for biotechnological withanolide production to unlock their pharmaceutical potential.